1997
DOI: 10.1073/pnas.94.6.2705
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intestinal uroguanylin/guanylin receptor-mediated responses by mucosal acidity

Abstract: Guanylin and uroguanylin are intestinal peptides that stimulate chloride secretion by activating a common set of receptor-guanylate cyclase signaling molecules located on the mucosal surface of enterocytes. High mucosal acidity, similar to the pH occurring within the f luid microclimate domain at the mucosal surface of the intestine, markedly enhances the cGMP accumulation responses of T84 human intestinal cells to uroguanylin. In contrast, a mucosal acidity of pH 5.0 renders guanylin essentially inactive. T84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
90
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 31 publications
9
90
0
2
Order By: Relevance
“…These peptides share sequence homology, have a tertiary structure stabilized by intrachain disulfide bonds, and exert their (patho)physiological effects by binding to GC-C and inducing cGMP accumulation. Uroguanylin, which is highly expressed in stomach, duodenum, and jejunum, is 100-fold more potent than guanylin at acidic pH (18,19). In contrast, guanylin is more abundant in ileum and colon and is 4-fold more potent than uroguanylin at a pH of 8.0 (18,19).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…These peptides share sequence homology, have a tertiary structure stabilized by intrachain disulfide bonds, and exert their (patho)physiological effects by binding to GC-C and inducing cGMP accumulation. Uroguanylin, which is highly expressed in stomach, duodenum, and jejunum, is 100-fold more potent than guanylin at acidic pH (18,19). In contrast, guanylin is more abundant in ileum and colon and is 4-fold more potent than uroguanylin at a pH of 8.0 (18,19).…”
mentioning
confidence: 93%
“…One hypothesis suggests a role for these peptides in the paracrine and autocrine regulation of f luid and electrolyte homeostasis in the intestine. Also, these peptides are expressed in extra-intestinal sites, including the kidney, suggesting that they may comprise one limb of an endocrine feedback loop that integrates the intestine into mechanisms regulating volume homeostasis (18,19). This function for GC-C is analogous to that for GC-A and GC-B and their agonists, the natriuretic peptides, which regulate f luid and electrolyte secretion in the kidney and play a central role in volume homeostasis (11).…”
Section: St Inhibits Proliferation Of Human Colon Carcinoma Cells Indmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using the T84 colon cell model may have provided some insights into some molecular features of the uroguanylin molecule that influence its biological activity. For example, the potency of uroguanylin remains high when the growth medium pH is reduced to an acidic condition, which in turn greatly reduces the potency of guanylin for activation of chloride secretion in T84 cells (18). The effects of pH appear to be manifest in the affinity of these peptides for interaction with R-GC-C.…”
Section: Properties Of Uroguanylin Versus Guanylinmentioning
confidence: 99%
“…Conversely, GN is more potent at pH 8 compared with pH 5 ( Figure 4). As this pH dependence affects the ligand/receptor interaction, it was suggested that the Nterminal ends of the UGN and GN molecules are responsible for this pH dependence (50). The duodenum secretes bicarbonate to neutralize the acidic pH of the stomach contents that enter the duodenum.…”
Section: Signaling Pathways Of Guanylin Peptides In the Intestinementioning
confidence: 99%